2018
DOI: 10.1002/ajs4.56
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal support for violence against women: What a population‐level survey of the Australian community can and cannot tell us

Abstract: Violence against women (VAW) is a serious and prevalent problem globally. Societal-level norms, practices and structures are among the factors contributing to it, sometimes referred to collectively as representing "cultures of support" for VAW. Understanding factors contributing to these cultures is important for prevention, but remains the subject of debate. Population-level surveys of attitudes toward VAW are one means to strengthen this understanding.Although there are a number of such surveys international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 63 publications
0
14
0
2
Order By: Relevance
“…However, neither of these measures have been adopted in Western countries. Items designed to gauge support for justifying violence in the NCAS have shown that in contrast to some countries participating in the WHO and DHS studies, only a very small proportion of Australians (less than 4%) is inclined to believe that violence against women can be justified in any circumstance (Webster et al., 2014). Arguably, the measure is not appropriately sensitive for the purposes of an Australian general community attitudes survey on violence against women, firstly because it focuses only on wife abuse (itself a very narrow definition of violence against women), and secondly because it asks respondents only about severe and physical forms of abuse as indicated by the language of ‘beating’.…”
Section: Attitudinal Support For Domestic and Intimate Partner Violencementioning
confidence: 99%
See 2 more Smart Citations
“…However, neither of these measures have been adopted in Western countries. Items designed to gauge support for justifying violence in the NCAS have shown that in contrast to some countries participating in the WHO and DHS studies, only a very small proportion of Australians (less than 4%) is inclined to believe that violence against women can be justified in any circumstance (Webster et al., 2014). Arguably, the measure is not appropriately sensitive for the purposes of an Australian general community attitudes survey on violence against women, firstly because it focuses only on wife abuse (itself a very narrow definition of violence against women), and secondly because it asks respondents only about severe and physical forms of abuse as indicated by the language of ‘beating’.…”
Section: Attitudinal Support For Domestic and Intimate Partner Violencementioning
confidence: 99%
“…As part of an ongoing policy commitment to reducing violence against women, successive Australian federal governments have funded three national surveys of community attitudes since 1995, with a further survey scheduled in 2016–2017. The most recent national community attitudes towards violence against women survey (hereafter, NCAS) includes questions that seek to measure (a) understandings or knowledge of violence against women, (b) attitudes towards violence against women (including attitudes that blame victims and/or excuse perpetrators), and (c) attitudes towards gender equality (VicHealth, 2014; Webster et al., 2014). The NCAS arguably acts as an important benchmarking tool which, at a broad societal level, provides an indication of change over time in each of the three key dimensions: knowledge of violence against women, attitudinal support for violence against women, and endorsement of gender equality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weak support for gender equality has been found to be associated with violence-supportive attitudes [ 28 ]. The indicator was based on the Gender Inequality in Relationships Scale [ 29 ] . Scores were derived from two items measured on 5-point Likert scales rated from Strongly Agree to Strongly Disagree, which were then combined and converted into scores out of 100.…”
Section: Methodsmentioning
confidence: 99%
“…Otros hallazgos menos sólidos han relacionado el respaldo a los mitos con otras variables como la edad y el nivel educativo. Con respecto a la edad, las evidencias acumuladas no son consistentes; mientras que algunos estudios no han encontrado que esta variable se relacione con la adhesión a los mitos y creencias sobre la violencia de género (Megías, Toro-García y Carretero-Dios 2018), otros sugieren que estas creencias disminuyen con la edad (Simon et al 2001), o bien que ambas variables presentan una relación curvilínea, de tal forma que las actitudes de apoyo hacia la violencia de género son mayores entre los jóvenes, más bajas en la edad adulta y nuevamente elevadas entre las personas más mayores (Webster et al 2018).…”
Section: Predictores De La Adhesión a Los Mitos Sobre La Violencia De Génerounclassified